Comparison of Overset Mesh with Morphing Mesh: Flow Over a Forced Oscillating and Freely Oscillating 2D Cylinder - Alletto, Michael (OpenFOAM® Journal, 2022)
Fluid structural interactions involve temporal change of the boundaries of the computational domain as a result of the fluid forces acting on the solid structure. In order to take into account this change, OpenFOAM offers two different methods: the overset method and the morphing mesh method. The morphing mesh method takes into account the boundary movement by changing the topology of the mesh but keeping the connectivity between cells unchanged. The overset methods consists in non overlapping meshes which are moving relative to a background mesh. Usually the meshes do not change the topology. The coupling between meshes is achieved by interpolation of the variables between the meshes. Both methods are compared with each other and reference experiments and simulation by taking a two-dimensional laminar flow around a cylinder. The results are found to agree reasonable well with the references. Both mesh types give similar results for similar number of cells.